Effect of Semolina Replacement with Amaranth Flour on Quality Characteristics of Functional Pasta - Sogand Alizadeh; Asiye Ahmadi-Dastgerdi; Sara Reisi; Fahimeh Ebrahimi Tirtashi; Maryam Zokaei; Shiva Tahriri (Journal of Food Quality, 2024)
Amaranth is one of the gluten-free pseudocereals and is suitable for celiac disease. This research aimed to investigate the effect of amaranth flour in concentrations of 0 (C), 10 (A10), 15 (A15), and 20% (A20) on the rheological, physicochemical, and sensory characteristics of functional pasta during 3 months. The prepared pasta was analyzed for its quality characteristics such as chemical composition, cooking loss, texture, color, and amylose leach out and was subjected to farinograph and extensograph tests and scanning electron microscopy (SEM). The results showed that the addition of amaranth flour weakens the rheological characteristics of pasta dough. Amaranth flour had a significant effect on the physicochemical properties of pasta (p<0.05). The lowest moisture content, fat, protein, and fiber were observed in the control sample, and the highest amounts were observed in the A20 sample. The moisture content decreased during storage. The control and A20 samples recorded the lowest and highest cooking loss, respectively. The addition of amaranth decreased the hardness, lightness (L), and yellowness (b∗) and increased the redness (a∗) of pasta. The amylose leach out in the cooking water of all amaranth pasta ranged from 2.03 g to 3.38 g/100 g which was lower than that of the control (4.95 g/100 g). The structure of control pasta is an interwoven network of gluten with many holes and swollen starch granules. A more uniform structure with fewer holes and a looser gluten network was observed in the microstructure of amaranth pasta. A10 treatment obtained the highest score of sensory evaluation. In conclusion, the amaranth flour has a good potential to be used in functional foods and gluten-free pasta. A20 was favorable in terms of physicochemical characteristics, and A10 was the best in terms of sensory characteristics.